Moment - Rotation characteristics of boltedc beam - to - column aluminium connections - French, Vandy (Department of Civil Engineering, 2014)
Structural aluminum provides a unique option to engineers by virtue of both its unique strength to weight ratio and its well known corrosion resistance properties. The development of the Eurocode 9 provides an insight to the design of aluminum structures based on results from various researchers worldwide. However the area of connections remains very sparse with regards to research material as compared to steel as provided by Eurocode 3 part 1-8. This work involves the analysis of the performance of aluminum end plate beam column connections with regards moment rotation behavior as well as the main connection classification criteria, strength, stiffness and ductility. A parametric study is done with the use of the non- linear finite elements program ADINA in which the effects of connection geometry is observed under incremental loading.